China's good war : how World War II is shaping a new nationalism - Mitter, Rana (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2020)
'Once sidelined from public memory, World War II is now a historical touchstone in China. Rana Mitter links the reassessment of the war to China's rising nationalism. At home, Chinese use the war to shape conflicted identities; abroad the war with Japan is now treated as a Chinese victory, a founding myth for a people destined to shape the global order'--
Introduction: war, memory, and nationalism in China -- Hot war, cold war : China's conflicts, 1937-1978 -- History wars : how historical research shaped China's politics -- Memory, nostalgia, subversion : how China's public sphere embraced World War II -- Old memories, new media : wartime history online and onscreen -- From Chongqing to Yan'an : regional memory and wartime identity -- The Cairo Syndrome : World War II and China's contemporary international relations -- Conclusion: China's long postwar
Includes bibliographical references and index
Keywords: Nationalism and collective memory -- China; Sino-Japanese War, 1937-1945 -- Public opinion; Chinese -- Attitudes; China -- Historiography